2007
DOI: 10.1624/105812407x173137
|View full text |Cite
|
Sign up to set email alerts
|

Step 1: Offers All Birthing Mothers Unrestricted Access to Birth Companions, Labor Support, Professional Midwifery Care

Abstract: The first step of the Ten Steps of Mother-Friendly Care insures that women have access to a wide variety of support in labor and during the pregnancy and postpartum periods: unrestricted access to birth companions of their choice, including family and friends; unrestricted access to continuous emotional and physical support from a skilled woman such as a doula; and access to midwifery care. The rationales for the importance of each factor and the evidence to support those rationales are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The restriction is contrary to the recommendation that every birthing mother should be allowed unrestricted access to the birth companions of her choice, including fathers, partners, children, family members, and friends [9]. Because of the resource poor nature of the study area and lack of doula services, one might have expected that labor support by husband and relations/ friends, which is an affordable and very accessible maternal health intervention, would have been adopted rapidly by the hospital management since it is beneficial to safe-motherhood and may not add to the administrative cost of the labor rooms.…”
Section: Discussionmentioning
confidence: 86%
“…The restriction is contrary to the recommendation that every birthing mother should be allowed unrestricted access to the birth companions of her choice, including fathers, partners, children, family members, and friends [9]. Because of the resource poor nature of the study area and lack of doula services, one might have expected that labor support by husband and relations/ friends, which is an affordable and very accessible maternal health intervention, would have been adopted rapidly by the hospital management since it is beneficial to safe-motherhood and may not add to the administrative cost of the labor rooms.…”
Section: Discussionmentioning
confidence: 86%
“…The presence of family members during child birth experiences has been recommended by WHO as one of the main aspects of humanized care [33]. The benefits of continuous one-on-one support by a companion during labor have also been noted by a Cochrane systematic review [34], and other research reviews in the past [35,36]. The presence of a companion or family members in the ICU or operating rooms has also been shown to provide positive psychological support for the pregnant women, whilst the care providers concentrate on the task of attending to more medical issues during the procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Hodnett, for example showed in one of his studies that women who had a companion who was not a member of the hospital staff present during labour and delivery, were less likely to require analgesia, and were generally more satisfied with their childbirth experience [ 34 ]. Leslie and Storton, in another research, also showed that the unrestricted presence of a birth companion of the women's choice, including husbands, partners, children, family members, and friends, was a key component regarding women's satisfaction during their birth experience [ 36 ]. In spite of the relevant research results, in Japan, husbands are still not always permitted to attend births, although in most centers, they will bypass this rule with the condition that they participate in the prenatal classes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dünya sağlık örgütü tarafından pozitif doğum eylemine ilişkin önerilerinde, doğumda doğum destekçisinin olması gerektiğini belirtmiştir 38 . Yapılan çalışmalar incelendiğinde doğumda, arkadaşın/partnerin/aile üyelerinden birinin bulunmasının kadında olumlu duygular geliştirdiği, pozitif yönde psikolojik destek sağladığı, spontan vajinal doğum oranları arttığı, anestezi-analjezi kullanımının azaldığı, doğum süresinin kısaldığı ve doğum deneyimlerinden daha memnun oldukları saptanmıştır 39,40,41,42,43 .…”
Section: Dünyada Obstetrik şIddetunclassified